Wywiad ustrukturyzowany w ocenie zaburzeń psychotycznych na przykładzie kwestionariusza SANS i SAPS = Structured clinical interviews for assessing psychotic disorders: diagnosis examples with SANS and SAPS questionnaires - Cyrkot, Tomasz; Gawęda, Łukasz; Szczepanowski, Remigiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This articles presents structured interviews and their usage in the diagnosis of psychotic disorders. The authors mainly discussed popular diagnostics tools such as Scale of Assessment for Negative Symptoms (SANS) and Scale of Assessment for Positive Symptoms (SAPS) that are combinations of structured interview technique and scale-based measurements of psychotic symptoms.
Keywords: wywiad ustrukturyzowany; zaburzenia psychotyczne; skale diagnostyczne SANS i SAPS; structured interview; psychotic disorders; SANS and SAPS scales